A Corpus-based Error Analysis of High School Students’ Written English: A Reflection on Noticing and Recasting - Hamada, Tarek Ibrahim Ibrahim (2008)
Students‟ errors need not be considered as symptoms of poor performance; on the contrary they should be treated as indicative healthy signs of an active learning process. This study was conducted to investigate whether high school students in the UAE were able to notice the grammatical and lexical errors in their writings. If so, how they were able to recast them taking the correctness of recasts into consideration. In addition, the most common unnoticed errors and the role of intralingual and interlingual transfer were other investigated areas. An analysis of a written corpus, which is a part of BALC (BUiD Arab Learner Corpus), of one hundred high school students‟ written paragraphs and essays was thoroughly analyzed. The results showed that students were able to notice 371 errors in their writings. These errors were reflected in their various methods of recast: deletions, insertions, and overwriting. Out of these errors, the students were able to correctly recast 272 (73%). Moreover the most common unnoticed grammatical and lexical errors were subject-verb agreement, negation, the use of modal verbs (can), and confusion of some words like „there- their‟, „its-it is‟, and „see-sea‟. Some of these errors were attributed to the negative transfer of the mother tongue like negation and some were attributed to the negative transfer from the target language like adding –s to verbs and nouns.